Intestinal epithelial cells preferentially attach to a biomatrix derived from human intestinal mucosa. - Hahn, U (1987)
Primary intestinal epithelial cells have a very short lifespan in vitro when cultured free of mucosal elements. Support of the basal plasma membrane by a more natural substrate may thus enhance the initiation of primary cell cultures. A cell free biomatrix consisting of native interstitial collagens, basement membrane fragments and microfibrils was extracted from the lamina propria of human intestinal mucosa. Immunofluorescence revealed the presence of collagens type III, IV, and VI and procollagens type I and III as well as fibronectin, laminin and undulin. Primary crypt cells of suckling mice displayed a significantly increased affinity to pepsin and collagenase solubilised intestinal biomatrix when compared with plastic and fibronectin. Colonies of primary crypt cells survived for up to four days and longer on pepsin solubilised biomatrix but only for 48 hours on fibronectin. The intestinal biomatrix preparation has proved to be a useful substrate for the initiation and prolongation of primary intestinal cell cultures.